Use of guided inquiry with interactive simulations to enhance students conceptual understanding and attitude towards learning forces, motion and mechanical energy - Estipular, Ma. Kristine L. (Animo Repository, 2017)
Teaching science requires use of models and experiments. However, not all schools in the Philippines have enough laboratory rooms and equipment to accommodate large classes. Using computers in teaching is one method that teachers use to provide mental models to students. This study is an action research aimed to determine if the use of guided inquiry with interactive simulation will enhance students conceptual understanding and attitude towards learning forces, motion and mechanical energy. A PDSA cycle was used to identify its effectiveness. It was conducted in a secondary high school in Quezon City for duration of four weeks. Two uppermost section from Grade 9 level were used as respondents in the study. The students attitude and instructional conceptions before and after the demonstration were gathered using the CLASS and Division-made concept test, respectively. Results of this study showed that there is a significant improvement on students conceptual understanding and attitude towards learning forces, motion and mechanical energy. This findings revealed that the use of guided inquiry with interactive simulation is an effective strategy in teaching physics.